2016
DOI: 10.1038/ajg.2016.417
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Secondary Prophylaxis With Vancomycin for Preventing Recurrent Clostridium difficile Infections

Abstract: Oral vancomycin appears as an effective strategy for decreasing the risk of further CDI recurrence in patients with a history of recurrent CDI who are re-exposed to antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
89
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 31 publications
3
89
0
7
Order By: Relevance
“…17. Surgery should be considered in those patients with CDI that do not respond to treatment in the first 24-48hrs; ce in patients who had a former rCDI episode (AHR, 0.47; 95% CI, 0.32-0.69; P <0.0001) [248]. This reduction was not observed for primary CDI episodes.…”
Section: Question 21 How Should a Patient With A CDI Recurrence Be Tmentioning
confidence: 94%
See 1 more Smart Citation
“…17. Surgery should be considered in those patients with CDI that do not respond to treatment in the first 24-48hrs; ce in patients who had a former rCDI episode (AHR, 0.47; 95% CI, 0.32-0.69; P <0.0001) [248]. This reduction was not observed for primary CDI episodes.…”
Section: Question 21 How Should a Patient With A CDI Recurrence Be Tmentioning
confidence: 94%
“…One of the first studies addressing this matter was the retrospective study performed by Carignan et al in 2016 [248] in which they studied 551 CDI episodes and observed that oral vancomycin prophylaxis decreased the risk of further recurren-patients treated with this drug. Addition of bezlotoxumab to fidaxomicin is another treatment option [183], but it would still be affected by the same cost issues faced by the antibiotic alone and more studies are needed to evaluate the efficacy of reducing rCDI with this combination.…”
Section: Question 22 In Patients That Have Recurrent Episodes Of CDImentioning
confidence: 99%
“…However, empirical antibiotic regimens including metronidazole were not associated with a protective effect against CDI in the ICU . Some data suggest that the empirical addition of oral vancomycin, at a dose of 125 mg or 250 mg twice/day as secondary prophylaxis, may lower the relative risk of CDI recurrence by 50% or more for patients on systemic antimicrobial therapy . However, these studies were limited by their retrospective design and inconsistent dosing strategies.…”
Section: Prophylaxismentioning
confidence: 99%
“…46 Some data suggest that the empirical addition of oral vancomycin, at a dose of 125 mg or 250 mg twice/ day as secondary prophylaxis, may lower the relative risk of CDI recurrence by 50% or more for patients on systemic antimicrobial therapy. [47][48][49] However, these studies were limited by their retrospective design and inconsistent dosing strategies. Very little data exist regarding the use of fidaxomicin for CDI prophylaxis outside of patients who have undergone hematopoietic stem cell transplantation.…”
Section: Prophylaxismentioning
confidence: 99%
“…Аналогичная проблема имеет место у пациентов, успешно завершивших терапию ИКД, но которым впоследствии были назначены системные ан тибиотики. Опубликованы результаты двух ретроспек тивных когортных исследований, в которых оценивался риск рецидивирующей ИКД у пациентов, которым по требовались последующие курсы антибиотикотерапии, и было проведено сравнение между теми, кто во время этого эмпирически получал терапию ванкомицином, и теми, кто не получал таковую [353,354]. В одном из этих исследований оценивались пациенты, получавшие антибиотикотерапию в пределах 90 дней от предыду щего эпизода, а в другом исследовании оценивались пациенты, которые были повторно госпитализированы (122 месяца спустя) и получали системную антибиоти котерапию.…”
Section: резюме по научному обоснованиюunclassified